(untitled) (Journal of Naval Architecture and Marine Engineering, 2023)
This paper presents a comprehensive study based on the results of a series of experiments conducted at different flow rates using micro-thinned sensors to obtain shear stress and velocity components around solid moving objects. The object dynamically represents marine vehicles and inflating boats through simplifications that ignore the effect of air in the object due to the complexity of capturing the viscoelastic behavior of such vehicles in simulations. Data obtained from experiments are compared with CFDsimulation results to observe the accuracy and impact of flow rate on different weights. The simulation uses the Reynolds-averaged Navier–Stokes formulation with the VOF method and the turbulence models SST k-ω. Three-dimensional transient simulations are performed using the overset grid technique to define the motion of the solid object in the flow field. Uncertainty analysis was carried out for both experiments and CFD simulations. The obtained shear stress and velocity results in the simulations are valid and acceptable for different flow rates on various weights. It is also concluded and demonstrated that weight has a specific impact on the shear stress and motion of the object. Journal of Naval Architecture and Marine Engineering, December, 2023, P: 53-76